2007
DOI: 10.1111/j.1574-6968.2007.00892.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylcholine synthesis inCrithidia deanei: the influence of the endosymbiont

Abstract: In this study, the role of phospholipid biosynthetic pathways was investigated in the establishment of the mutualistic relationship between the trypanosomatid protozoan Crithidia deanei and its symbiotic bacterium. Although the endosymbiont displays two unit membranes, it lacks a typical Gram-negative cell wall. As in other intracellular bacteria, phosphatidylcholine is a major component of the symbiont envelope. Here, it was shown that symbiont-bearing C. deanei incorporates more than two-fold (32)Pi into pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 32 publications
(79 reference statements)
1
18
0
1
Order By: Relevance
“…Interestingly, this last step of the pathway is not found in the S. culicis endosymbiont. Importantly, both symbionts lack genes that encode proteins of PC biosynthetic pathways, reinforcing the idea that this phospholipid is mainly obtained from the host protozoa [5]. Remarkably, phoshpatidylglycerophosphatase A, which produces the intermediate phosphatidylglycerol necessary for cardiolipin biosynthesis, was not found in either protozoa but is present in both symbionts.…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…Interestingly, this last step of the pathway is not found in the S. culicis endosymbiont. Importantly, both symbionts lack genes that encode proteins of PC biosynthetic pathways, reinforcing the idea that this phospholipid is mainly obtained from the host protozoa [5]. Remarkably, phoshpatidylglycerophosphatase A, which produces the intermediate phosphatidylglycerol necessary for cardiolipin biosynthesis, was not found in either protozoa but is present in both symbionts.…”
Section: Resultsmentioning
confidence: 68%
“…The sphingophospholipid (SPL) content in A. deanei and its symbiont has been previously described, with phosphatidylcholine (PC) representing the major SPL in the host, whereas cardiolipin predominates in the symbiotic bacterium [5], [80]. The synthetic pathway of phosphatidylglycerol from glycerol phosphate is present in both host trypanosomatids (Table S16).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This agreed with our previous works, which showed that PE is an essential constituent of the symbiotic bacterium membranes (Palmié‐Peixoto et al ., ). Once isolated from the protozoan, the symbiont is able to produce phospholipids, especially PE, independently of the host cell (Azevedo‐Martins et al ., ). However, it is noteworthy that the symbiosis in trypanosomatids is an obligatory relationship with extensive metabolic exchanges (reviewed by Motta, ) and that the bacterium may obtain part of PC or PC precursors from the host (Azevedo‐Martins et al ., ).…”
Section: Discussionmentioning
confidence: 99%